2007
DOI: 10.1111/j.1469-8137.2007.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the late stages of the tomato–Phytophthora parasitica interactions through histological analysis and generation of expressed sequence tags

Abstract: Summary• The oomycete Phytophthora parasitica is a soilborne pathogen infecting numerous plants. The infection process includes an initial biotrophic stage, followed by a necrotrophic stage. The aim here was to identify genes that are involved in the late stages of infection.• Using the host tomato and a transformed strain of P. parasitica expressing the green fluorescent protein (GFP), the various infection steps from recognition of the host to the colonization of plant tissues were studied. This late stage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 66 publications
3
65
0
Order By: Relevance
“…Moreover, it has been demonstrated that biomass of Phytophthora spp. such as P. infestans and P. ramorum in infected tissues is generally low 29 . Other possible reason is that the disease expressing materials tested here might not be caused by Phytophthora spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that biomass of Phytophthora spp. such as P. infestans and P. ramorum in infected tissues is generally low 29 . Other possible reason is that the disease expressing materials tested here might not be caused by Phytophthora spp.…”
Section: Discussionmentioning
confidence: 99%
“…nicotianae [15,16] and P. brassicae [17] . In this paper we extend the use of GFP to P. sojae using the CaCl 2 /PEG-mediated transformation method.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been successfully used for the expression of marker genes such as gus and gfp in Phytophthora spp. [12][13][14][15][16][17][18] . Here, we describe the first successful transformation of the oomycete P. sojae with the reporter gene gfp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations